Konsep Kesehatan Fisik dan Mental Perspektif Al-Qur’an dalam Konteks Kehidupan Modern - Widianti, Anyta; Galib, M.; Abubakar, Achmad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This paper aims to examine the concept of physical and mental health from the perspective of the Qur'an, which emphasizes the importance of balancing both in human life. The purpose of this study is to reveal the Qur'anic view on health and how the teachings in this holy book can provide guidance in maintaining both physical and mental health. The methodology used in this research is literature study, analyzing various Qur'anic verses related to the topic. The findings indicate that the Qur'an provides clear guidance on the importance of maintaining health, both physical and mental, which remains relevant to be applied in modern life. Given the increasingly complex health challenges in the modern era, it is important to link the teachings of the Qur'an with human needs in maintaining physical and mental well-being, as explained through the guidance provided in the Qur'an and the Hadith of Prophet Muhammad SAW.